In vitro antagonistic screening of the endophytic fungi from the inner bark of Cinnamomum mercadoi Vidal against the fungal phytopathogen Sclerotinia sclerotiorum - Amano, Keith Gabriel D. (Division of Natural Sciences and Mathematics, University of the Philippines Visayas Tacloban College, 2017)
Due to massive concerns about the use of toxic agricultural chemicals as a form of controlling the ever-dynamic propagation of plant pathogens, the search for new grounds in providing safer alternatives have led to recognize biological pesticide agents. The potential use of various pesticide sources from microbe-based agents has provided a new avenue for research in order to mitigate effects of pesticide use. In connection, this study investigated the antagonistic bioactivity of the endophytic fungi isolated from the bark of Cinnamomum mercadoi against common crop fungal pathogen: Sclerotinia sclerotiorum. Through dual culture method, the isolates were tested against the pathogen and were incubated for 5 days. Results showed non-inhibiting effects of the bark endophytic fungal isolates from C. mercadoi as observed in the absence of the zones of inhibition in each setup. But further analysis through microscopy of the area of Pestalotiopsis sp. culture and of S. sclerotiorum culture showed otherwise. The interaction displayed Pestalotiopsis sp. providing hyperparasitic mechanisms though in a minimal effect. Albeit in an efficacy of a certain compund in small concentrations, such interaction still indicates the presence of antifungal properties.